Analytical Study of the Effect of Node Mobility and Synchronization Messages Frequency on the Performance of Reactive Protocols in MANET Networks - بليلو, محمد (Latakia University Journal -Engineering Sciences Series, 2023)
Today, MANET networks occupy an important space in the field of information networks and communications due to its wide spread in many scientific and applied fields, in addition to its important applications in various civil and military fields. It can be created using different wireless transmission and reception techniques, which reduces the cost of building and establishing communication in the network and makes it flexible and able to change its architecture and topology dynamically and adaptively. Assurance of an appropriate quality of service in MANET networks is one of the most important challenges it faces, which prompted researchers around the world in this field to focus on studying and analyzing the performance of the parameters affecting the quality of service in order to reach the ability of operating these networks in real time or in a near real time. Acceptable, and one of the most important parameters of service quality is the time delay and it must be kept as small as possible. The second parameter is the packet delivery ratio, which gives an impression of the extent of the arrival of the packets sent from the source nodes to the target nodes and must be kept as large as possible. In this research, a comprehensive and systematic analytical study was presented for the effect of the mobility of nodes in the network and the frequency of sending synchronization messages between nodes in the PUMA protocol, which is one of the types of reactive protocols, by choosing a set of realistic and closest scenarios for the configuration and settings of MANET networks, and the results were compared according to the delay and packet delivery ratio in order to reach the best settings and configurations for MANET networks in the various surrounding working conditions that lead to raising the level of quality of service provided as possible.